A new fossil eomeropid (Insecta, Mecoptera) from the Jiulongshan Formation, Inner Mongolia, China - Zhang, Junxia (2011)
A new genus and species of eomeropid, Jurathauma simplex n. gen., n. sp., is described from the Middle Jurassic of Inner Mongolia, China. It can be distinguished from all known eomeropid genera by a combination of these characters: two rows of cells formed by crossveins between costal margin and ScP; RP + MA with five branches; MP with five branches; and three anal veins. The presence of this new species and Tsuchingothauma shihi Ren & Shih, 2005 of the same family in this locality suggests the early diversification of eomeropids with cockroach-like body during the Middle Jurassic.